2019
DOI: 10.1128/jvi.02247-18
|View full text |Cite
|
Sign up to set email alerts
|

An Epigenetic Journey: Epstein-Barr Virus Transcribes Chromatinized and Subsequently Unchromatinized Templates during Its Lytic Cycle

Abstract: The Epstein-Barr virus (EBV) lytic phase, like those of all herpesviruses, proceeds via an orderly cascade that integrates DNA replication and gene expression. EBV early genes are expressed independently of viral DNA amplification, and several early gene products facilitate DNA amplification. On the other hand, EBV late genes are defined by their dependence on viral DNA replication for expression. Recently, a set of orthologous genes found in beta-and gammaherpesviruses have been determined to encode a viral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 94 publications
0
34
0
Order By: Relevance
“…5 and 7). We note that the regulation of transcription of late proteins in gammaherpesvirus infection is complex and appears to reflect changes in histones, CpG methylation, and the formation of replication centers in productively infected cells, as recently reviewed (36). An important role for PERK in inhibiting the translation of viral proteins has been detailed in other systems (37).…”
Section: Discussionmentioning
confidence: 89%
“…5 and 7). We note that the regulation of transcription of late proteins in gammaherpesvirus infection is complex and appears to reflect changes in histones, CpG methylation, and the formation of replication centers in productively infected cells, as recently reviewed (36). An important role for PERK in inhibiting the translation of viral proteins has been detailed in other systems (37).…”
Section: Discussionmentioning
confidence: 89%
“…We next tested whether ORF66 plays a role in replication of the viral genome. It is well established that late gene transcription is licensed by the initiation of viral genome replication (15-17). Although it has been previously reported that other vTA mutants do not exhibit a defect in viral genome replication (6, 8-10), we recently reported that mutations in ORF24 result in a ∼6-fold defect in viral genome replication (1).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple layers of epigenetic regulation enable EBV to establish latency in newly-infected B-cells, in which a small number of viral encoded proteins and viral non-coding RNAs reprogram infected cell metabolism, growth and survival pathways (79). Within 3 days of infection, quiescent B-cells are reprogramed to become rapidly growing lymphoblasts that divide as frequently as every 8 hours (1013).…”
mentioning
confidence: 99%
“…Plasma cell differentiation is a trigger for EBV lytic reactivation. Induction of two viral immediate early gene transcription factors, BZLF1 and BRLF1, induce nearly 30 early genes important for production of lytic genomes (10, 14, 15). How these newly synthesized EBV genomes evade chromatinization by host histone loaders, including the heterotrimeric Chromatin Assembly Factor 1 (CAF1) complex that delivers newly synthesized H3/H4 dimers to host replication forks, is only partially understood (16, 17).…”
mentioning
confidence: 99%
See 1 more Smart Citation